Pemodelan Zero Inflated Negative Binomial (ZINB) Pada Kasus Jumlah Bepergian Penduduk Provinsi Sulawesi Tengah - I T Utami (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2020)
Traveling is something that has been done by every resident, especially the people of Central Sulawesi province. The people of Central Sulawesi province who travel have a certain purpose either because of their own desires or following others. The number of people traveling from Central Sulawesi Province can be analyzed using the zero inflated negative binomial regression method (ZINB). ZINB regression is a method used to model calculated or discrete data with many zero values ​​on the response variable (zero inflation) and overdispersion occurs. The result shows that the factors affecting the number of people traveling population from the Central Sulawesi Province are age (X1), the people who have jobs in mining and quarrying (X32), the people who have jobs in electricity and gas (X34). The zero inflated negative binomial (ZINB) regression model is better at modeling cases of the number of people traveling in Central Sulawesi Province in 2016 compared to the Poisson regression model because it has the smallest AIC value.